Analisis Intensi Pembelian Produk Ramah Lingkungan pada The Body Shop Indonesia - Ahmad Satya Wicaksana; Camilla Janette Jasrin; Elkana Satria Nugroho; Yohanna Satya Yohanna (Universitas Prasetiya Mulya, 2019)
The purpose of this study is to determine the impact of green brand knowledge, consumer’s attitude towards green product and green brand positioning to the green product purchase intention The Body Shop. Questionnaires with 17 instruments are being distributed to 304 respondent in Jakarta, Depok, Bogor, Bekasi and Tangerang to gain the data. The data then being processed using computer software SPSS. Based on the research, green brand knowledge has the biggest influence on green product purchase intention. Cosmetic companies like The Body Shop may use promotion strategy to improve consumer’s green product knowledge.